2001
DOI: 10.1038/sj.onc.1204799
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of matrix metalloproteinase-2 gene expression and invasion in human glioma cells by MMAC/PTEN

Abstract: Human gliomas are highly invasive, and remain to be a major obstacle for any e ective therapeutic remedy. Among many other factors, gliomas express elevated levels of matrix metalloproteinases (MMPs), which have been implicated to play an important role in tumor invasion as well as neovascularization. The tumor suppressor gene mutated in multiple advanced cancers/ phosphatase and tensin homologue (MMAC/PTEN) has been shown to inhibit cell migration, spreading, and focal adhesion. In this study, we determined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 45 publications
4
65
1
1
Order By: Relevance
“…Also, cell movement, which is necessary for invasion, was not affected significantly by the hyaluronan oligomers in two of the three invasive glioma cells tested. Another parameter that is important for invasion is production of matrix metalloproteinases, [41][42][43] whose production is regulated by the PI3K pathway 38 -40 and is stimulated by treatment with polymeric hyaluronan. 44,45 In glioma cells, hyaluronan stimulation of gelatinase B is inhibited by the tumor suppressor, PTEN, at least in part because of inactivation of focal adhesion kinase rather than the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cell movement, which is necessary for invasion, was not affected significantly by the hyaluronan oligomers in two of the three invasive glioma cells tested. Another parameter that is important for invasion is production of matrix metalloproteinases, [41][42][43] whose production is regulated by the PI3K pathway 38 -40 and is stimulated by treatment with polymeric hyaluronan. 44,45 In glioma cells, hyaluronan stimulation of gelatinase B is inhibited by the tumor suppressor, PTEN, at least in part because of inactivation of focal adhesion kinase rather than the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of brevican is absent from low-invasive 9L gliosarcomas (Zhang et al, 1998) but is abundant at the invasion front of G261 glioblastomas, as is the proinvasive metalloproteinase-2 (supplemental Fig. 1e-g, available at www.jneurosci.org as supplemental material) (Koul et al, 2001).…”
Section: Characterization Of the Glioblastoma Modelmentioning
confidence: 99%
“…In vitro studies with glioma cell lines deficient in PTEN expression showed that inhibitors of PI3K (LY294002 and wortmannin), or overexpression of PTEN, reduced cell invasiveness in vitro, and this was associated with reduced activity of matrix metalloproteinases including MMP2 and MMP9 (Kubiatowski et al, 2001;Koul et al, 2001).…”
Section: Migration and Invasionmentioning
confidence: 99%